Male immunity to the chlamydial 60 kDa heat shock protein (HSP 60) - associated with semen quality? - Eggert-Kruse, Waltraud; Batschulat, K.; Demirakça, Traute; Strowitzki, Thomas (Andrologia, 2015)
The role of Chlamydia trachomatis for male infertility is a matter of constant debate. It is assumed that in its persistent form this pathogen may produce high levels of 60 kD heat shock protein (Chlam HSP60). Cross-reactivity between epitopes of the bacterial and human HSPs, involved in many steps of the reproductive process, might induce an autoimmune response with potential impairment of semen quality and sperm fertilising capacity. This prospective study included asymptomatic males of a total of 128 unselected subfertile couples (median duration of infertility 3 years) to determine the clinical relevance of male immunity to Chlam HSP60 during infertility investigation. After medical history and clinical examination of both partners, serum antibodies (Ab) to Chlam HSP60 were determined. Same day semen quality evaluation included microscopical standard sperm analysis, determination of seminal white blood cells (WBC) and of antisperm Ab (ASA) of the Ig G- and Ig-A class (mixed antiglobulin reaction, MAR), microbial screening and examination of sperm functional capacity. Sperm/mucus interaction was tested in vitro and in vivo. Simultaneously, patients′ female partners were tested for Chlam HSP60 Ab and results were compared with a standard serology evaluation for antichlamydial IgG Ab. The presence of ChlamHSP60 Ab (positive in 24% of males) was not significantly associated with semen quality, seminal WBC and antisperm AB of the IgG- or Ig A-class, the outcome of the microbial screening nor with sperm functional capacity and results of sperm/mucus interaction testing in vitro and in vivo. Chlam HSP60 Ab were significantly more frequent in female partners of Chlam HSP60 Ab-positive men, and results correlated with the outcome of standard chlamydial serology evaluation. In conclusion, when serum Chlam HSP60 Ab are used as marker, male immunity to the chlamydial 60 kD heat shock protein is not associated with semen quality, sperm functional capacity and other clinically relevant parameters of male fertility.